2022
DOI: 10.1007/s11136-022-03187-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health-related quality of life in Parkinson’s disease: the impact of overlap between health-related quality of life and clinical measures

Abstract: Purpose This study aimed to determine predictors of health-related quality of life (HRQoL) in Parkinson's disease (PD) and to explore their predictive value before and after controlling overlapping items between HRQoL and clinical variables. Methods One hundred and eight PD patients underwent motor, anxiety, depression, apathy, fatigue, and neurocognition assessment. HRQoL was assessed by the Parkinson’s Disease Questionnaire-39 (PDQ-39). In order to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 72 publications
0
2
0
2
Order By: Relevance
“…Being unable to accomplish these tasks may reduce autonomy and negatively impact QoL. Patients with other medical conditions have had their QoL and functional status predicted by their neurocognitive performance 36–38,63–65 . The participants with PCC in the present study, regardless of the severity of acute COVID‐19, showed impairments in global cognition (MoCA), verbal memory (RAVLT), and mental speed processing–executive function (Digit symbol test, TMT B, SCWT) compared with the control group.…”
Section: Discussionmentioning
confidence: 68%
“…Being unable to accomplish these tasks may reduce autonomy and negatively impact QoL. Patients with other medical conditions have had their QoL and functional status predicted by their neurocognitive performance 36–38,63–65 . The participants with PCC in the present study, regardless of the severity of acute COVID‐19, showed impairments in global cognition (MoCA), verbal memory (RAVLT), and mental speed processing–executive function (Digit symbol test, TMT B, SCWT) compared with the control group.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, several devastating symptoms, particularly non-motor symptoms such as fatigue, sleep disturbances, anxiety, depression, or impaired autonomic regulation cannot be effectively treated. However, these symptoms are important predictors of health-related quality of life in PD [7]. In addition to pharmacological strategies, deep-brain stimulation (often of the subthalamic nucleus and thereby dopaminergic neuronal networks) has emerged as a therapy of choice for a subgroup of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Apresenta-se com duas categorias principais de sintomas, quais sejam, os sintomas motores e sintomas não motores. Apesar de, no conhecimento popular, o parkinsonismo ser associado principalmente aos tremores, este pode não estar presente, sendo a bradicinesia um sintoma mais prevalente e de desenvolvimento mais precoce (SANCHEZ-LUENGOS et al, 2022). Há, na maioria dos pacientes com Parkinson, a lentificação na execução de movimentos, com alterações de sua quantidade e amplitude, bem como alterações na mímica facial, a qual geralmente fica diminuída/apática (PFEIFFER, 2016).…”
unclassified
“…Brazilian Journal of Health Review, Curitiba, v. 6, n. 2, p. 6421-6434, mar./apr., 2023 A respeito do impacto na qualidade de vida, dentre os sintomas não-motores da DP, a fadiga é um dos objetivamente mais importantes. Em um estudo recente, de 2022, análises regressivas desses sintomas associadas à pontuação no PDQ-39 (Parkinson's Disease Questionnaire-39), indicam que o parâmetro "qualidade de vida associada à saúde" -HRQoL (Health Related Quality of Life) apresenta índice de 16,5% relacionado exclusivamente à fadiga(SANCHEZ-LUENGOS et al, 2022). No mesmo sentido, num estudo transversal italiano, pode-se perceber que, além da maior prevalência de fadiga nos pacientes com DP, há também associação desse sintoma com pontuações mais altas na UPDRS e pior pontuação na PQD-39.…”
unclassified